Desenvolvimento e transferência de tecnologia de instituições científicas e tecnológicas para o setor produtivo: estudo de caso do Estado do Paraná - Rau, Carina (2020)
This study explores technological development and its transfer in the context of cooperation between scientific and technological institutions (STIs), represented mostly by universities; and business (UB). The motivation for research arose from the finding that most technology transfer studies are not very clear on how the process of technology development takes place. In this way, the general objective of this work is to propose a framework for the development and transfer of STI technology to the productive sector, using the State of Paraná (Brazil) as a case study. This research is predominantly qualitative, with primary data collection in three phases: i) survey of data on intellectual property applications and technology transfers from 16 STIs from Paraná selected for the study; ii) sending a questionnaire to researchers inventors of intellectual property applications in order to understand the process of developing protected and transferred and non-transferred technologies; iii) conducting interviews with the three STIs with the highest number of transfers and with the companies receiving the highest number of technologies in each of them. As a result of the research, a framework is proposed combining elements of the literature with empirical elements obtained in the case study conducted in Paraná, with its heterogeneities and particularities. This STI Framework for Development and Technology Transfer has four elements: mission, coordination, policy and sector. The mission dimension expresses the need for institutional and personal adjustment to fit UB interactions in the institutional mission, focused on innovation. The coordination element defends that the instigation of cooperation for the development and technology transfer can be done by the researchers, with the coordination of the companies. The institutional innovation policy must be revisited in STIs in order to encourage its human capital to conduct research in strategic sectors. It is inferred, from the case study in Paraná, that developing demand-driven technologies of the productive sector favors their transfer to society, and that the STI´s human capital plays a key role in the beginning of successful interactions.